COLLABORATION BETWEEN INDUSTRY AND GOVERNMENT IN REALISING A SUSTAINABLE ECONOMY 5.0 - Loso Judijanto; Al-Amin (CV. ADIBA AISHA AMIRA, 2025)
Collaboration between industry and government plays a vital role in realising a sustainable Economy 5.0, where synergy between people and technology is the main driver of progress. This vision promotes knowledge-based economic development and advanced technology, which requires close cooperation between the private sector and the government. In this collaboration, industry focuses on digital innovation and technology, while the government creates regulations and a conducive environment. This combination not only improves efficiency and global competitiveness, but also promotes inclusive policies that can address social and environmental challenges. The responsible and environmentally friendly implementation of technological solutions is essential in this joint effort, ensuring that economic growth is not only materially beneficial but also sustainable for society and the environment.